Konsep Tawakal dalam Al-Qur'an dan Relevansinya Terhadap Pendidikan - faizah, misbahul; Syamsul Arifin (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2023)
Tawakal is trying our best accompanied by prayer, then leaving the results to Allah Swt. The concept of tawakal is one of the fundamental concepts in Islam that teaches to fully trust in Allah SWT. As a source of strength and a way out of all difficulties. This concept does not only apply in spiritual aspects, but can also be applied in various aspects of life, including in the context of education. This article will further discuss the concept of tawakal in the Qur'an and its relevance to education. It is hoped that this article can provide a better understanding of the concept of tawakal and how it is applied in the context of education. The researcher in this article intends to explore how tawakal can affect mental health, psychological resilience, and adaptation to life challenges, especially in the context of education. In the context of education, the concept of tawakal can help educators and students to achieve success and success in the teaching-learning process. By understanding the concept of tawakal, educators and students can become obedient and noble individuals in their daily lives and can achieve success in various aspects of life.